A thematic review on relationship between recovery perception towards place attachment in urban environment - Chen, Yurui; Shukor, Shureen Faris Abdul; Muthuveeran, Adam Aruldewan S. (Editura Universitati din Oradea, 2023)
Place attachment is often seen as a resource for coping with health recovery, especially in the post-pandemic period. The purpose of this review was to systematically review the variables, research frameworks, and interactions related to place attachment and recovery perceptions. This paper reviewed 53 papers from 2020 to 2023 on place attachment and recovery perception using ATLAS.ti. Existing research confirms that there are differences in the degree of attachment and recovery in different types of urban environments. This paper encourages the integration of information between different disciplines, such as urban planning specialists, environmental psychologists, and public health experts, to further improve the urban environment.